Relationship of brachial artery responsiveness parameters to left ventricular diastolic dysfunction in patients with rheumatoid arthritis - Elena Evgenyevna Myasoyedova; S E Myasoyedova; S V Obzherina; N D Svyatova (Научно-практическая ревматология, 2012)
Objective: to study vascular responsiveness parameters in rheumatoid arthritis (RA) patients with and without left ventricular diastolic dysfunction (DD) and to identify the predictors of DD among the characteristics of vascular responsiveness in RA patients having no cardiovascular diseases. Subjects and methods. The investigation enrolled 61 RA patients (mean age 47.1 years; 87% of females) without cardiovascular comorbidity. All the patients underwent standard echocardiographic study with diastolic function assessment in accordance with the 2005 European Society of Cardiology guidelines. Vascular responsiveness was studied using brachial artery Doppler ultrasonography in a 5-minute compression test. Associations between vascular responsiveness parameters and DD were studied using logistic regression models and adjusting for patient gender and age. Results and discussion. DD was found in 35 (57%) patients. The parameters of vascular responsiveness in RA patients with DD differed from those in RA patients without DD. The decrement in blood flow volumetric velocity in the brachial artery 10 sec (odds ratio [OR] 0.8; 95% confidence interval [CI] 0.7-0.97), and 1 min (OR 0.7; 95% CI 0.5-0.96) after decompression and the relative increment in blood flow volumetric velocity within the first minute after decompression (OR = 0.9; 95% CI 0.9-0.99) were associated with the presence of DD. There were no statistically significant associations of the changes in brachial artery diameter with DD. Conclusion. The decrement in blood flow volumetric velocity in the brachial artery, as evidenced by the compression test, is associated with DD in RA patients without cardiovascular diseases. The association of impairments in vasomotor and diastolic functions in RA shows the commonness of pathogenic mechanisms for the development of these changes and opens considerable scope for the earlier diagnosis of DD according to the results of the study of vascular responsiveness.